Identity-safe or threatening? Perceptions of women-targeted diversity initiatives. (August 2018) - Cundiff, Jessica L.; Ryuk, Sohee; Cech, Katie
One strategy for addressing gender disparities in STEM and leadership focuses on women-targeted diversity initiatives, such as women's networking groups and women's leadership development programs. Although well intentioned, targeting diversity initiatives specifically toward women instead of all employees may unwittingly make workplaces appear unwelcoming and biased to prospective employees. To test this notion, undergraduate women and men read a recruitment brochure for a company that framed its diversity initiatives as either targeting women employees or all employees. Both women and men felt less social fit and comfort with the company and were more concerned about being treated negatively and unfairly when diversity initiatives were framed as women-targeted rather than all-inclusive. These results held regardless of whether the company was portrayed as male-dominated or gender equitable (Study 1, N = 117). However, results were somewhat attenuated for women, but not men, when the women-targeted program was portrayed as initiated and led by women employees rather than upper management (Study 2, N = 152). Overall, our results suggest that diversity initiatives may more effectively convey identity safety to both women and men when framed in a way that includes all employees rather than targeting only women.